PERSPECTIVES OF THE EURO AREA SOVEREIGN DEBT CRISIS FOR THE BRAZILIAN ECONOMY - Moller, Horst Dieter (2013)
The objective of this article is to show the perspectives of the euro area sovereign debt crisis for the Brazilian economy. The euro area sovereign debt crisis, beginning in 2010, could be seen as fallout of the global financial crisis of 2008/09. The ways to the crisis for Portugal, Ireland, Italy, Greece and Spain were different: Credit booms and housing bubbles, banking crises, unsustainable public indebting. The impacts on Brazil were felt in 2011 and 2012 with the Brazilian economy almost stagnating. The article evaluates the impacts of the global financial crisis 2008/09 on the Brazilian economy through real and monetary channels, as well as through the contagion of expectations, to find similarities with the present crisis. The main influence was the fall of Brazilian exportations and the credit crunch following the failure of Lehman Brothers in September 2008. The article supposes that the impacts of the euro area crisis shall be less problematic than that of the global financial crisis of 2008/09, because exportations are geographically more diversified and a credit crunch could be confronted by the BNDES and the public banks in Brazil. But the main argument is that the stability of Brazilian institutions, the geographical diversification of exportations and the increasing demand for commodities by the emerging markets in Asia will soften the impacts of the present crisis for Brazil, supposing that contagion of the sovereign debt crisis in the euro area will not expressively hit the more important economic powers in Europe and the world. The causes of the stagnating Brazilian economy in 2012 probably are not only the problems in the euro area.